Analytical transport network theory & structural mechanics: Towards computationally inexpensive multi-functional materials design. (September 2020) - Cocco, Alex P.; Grew, Kyle N.
Highlights: Transport and mechanical analyses of complex, 3D network structures. Computationally inexpensive, interpretable, and hierarchical framework. Opportunity for future integration into topology optimization/machine learning. Abstract: Analytical transport network (ATN) theory is extended to account for static, structural mechanics. The extension provides a consistent, computationally economical, and interpretable formalism for examining morphological/topological trade-offs relevant to the design of multi-functional materials. The approach is demonstrated through application to over 100, 000 computationally-generated lattice structures consisting of non-uniform channels. It is orders of magnitude faster and less memory intensive than finite element analysis. This, along with its compact mathematical formalism, present the opportunity for future integration into multi-functional characterization/design frameworks (e.g., topology optimization and machine learning). GRAPHICAL ABSTRACT: Image, graphical abstract